(untitled) (ModaPalavra e-periódico, 2023)
This study aims to demonstrate the relevance of the Fashion sector in the Creative Industry. This research becomes relevant in the investigation of new concepts about the area, thus outlining the classifications on the creative sectors and their definitions, in addition to presenting important data from the Fashion sector, through a bibliographical research, of an exploratory nature and qualitatively analyzed. From this, one sees the relevance of the Fashion sector, in dialogue with Design, among the creative sectors, because before the emergence of the term Creative Industry they were already selling goods and services developed from creativity.